Structural Simulation of Mg2SiO4 under Compression - Hung Son, Nguyen; Hoang Anh, Nguyen (VNU Journal of Science: Mathematics - Physics; Vol 36 No 4, 2020)
The microstructure in Mg 2 SiO 4 glass under high compression is studied by molecular dynamic method. This work revealed the correlation between pair radial distribution functions (PRDF) of Si-Si pair and bond angle distribution (BAD) of Si-O-Si and focus on clarifying the split peak of Si-Si PRDF. Moreover, visualizing the bonds of Si-Si at different pressures show changing of Si-Si bonds with pressure. In particularly, as increasing pressure, it forms corner-sharing, edge-sharing and face-sharing bond between SiO x coordination units results in the first peak splitting of Si-Si PRDF at high pressure. The results of Si-Si’s PRDF have also been analyzed and explained in detail.